2018
DOI: 10.1038/s41416-018-0113-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antioxidant intake and the risk of developing Barrett’s oesophagus and oesophageal adenocarcinoma

Abstract: Data supports a role for dietary antioxidants prevent BO and OAC, perhaps at the earlier stages of carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…Vc is one of the commonly used antioxidants. Several studies have demonstrated that Vc can decrease the risk of developing gastrointestinal diseases via reducing oxidative stress response 50,51 . In the present study, we found that rats given Vc had higher contents of CAT and SOD, as well as a higher mRNA expression level of GCLC.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Vc is one of the commonly used antioxidants. Several studies have demonstrated that Vc can decrease the risk of developing gastrointestinal diseases via reducing oxidative stress response 50,51 . In the present study, we found that rats given Vc had higher contents of CAT and SOD, as well as a higher mRNA expression level of GCLC.…”
Section: Discussionsupporting
confidence: 66%
“…Several studies have demonstrated that Vc can decrease the risk of developing gastrointestinal diseases via reducing oxidative stress response. 50,51 In the present study, we found that rats given Vc had higher contents of CAT and SOD, as well as a higher mRNA expression level of GCLC. Meanwhile, the administration of Vc increased the protein expression levels of p-Nrf2, p-p38 and JNK.…”
Section: Discussionsupporting
confidence: 64%
“…This is because cancer cells have redox regulation genes, suggesting that low ROS levels are required for their survival; however, the therapeutic approach may be crucial to treating this pathology. Nevertheless, in clinical trials has been shown that antioxidant consumption might be beneficial [ 167 , 168 , 169 , 170 , 171 , 172 ] or have no effect [ 167 , 172 , 173 , 174 ], as it is suggested to depend on the metabolic demand of the individual.…”
Section: Inflammation In Cancermentioning
confidence: 99%
“…[ 7 ] Currently, vitamin C (Vc) is the most commonly used supplement for OSD clinical therapy. Several studies have demonstrated that the intake of Vc can reduce the risk of developing digestive system diseases [ 8‐9 ] and reduce liver damage by regulating the oxidative stress response. [ 10 ] However, the long‐term or incorrect intake of Vc supplement is associated with several side effects, such as increased gastric acid production, [ 11 ] poor oral utilization, and increased risk of developing kidney stones.…”
Section: Introductionmentioning
confidence: 99%